Ablation of the Ligament of Marshall and Left Stellate Ganglion Similarly Reduces Ventricular Arrhythmias During Acute Myocardial Infarction. (May 2018) - Liu, Shan; Yu, Xiaomei; Luo, Da; Qin, Zhiliang; Wang, Xiaoying; He, Wenbo; Ma, Ruisong; Hu, Huihui; Xie, Jing; He, Bo; Lu, Zhibing; Jiang, Hong
Abstract : Background: Sympathetic denervation exerts protective effects against ventricular arrhythmias (VAs) induced by acute myocardial infarction. The results of a previous study indicated that the distal part of the ligament of Marshall (LOMLSPV ) might be a sympathetic conduit between the left stellate ganglion (LSG) and the ventricles. The present study was designed to compare the effects between LSG and LOMLSPV ablation on ischemia-induced VAs. Methods: Twenty-nine dogs were randomly divided into sham ablation group (group 1, n=9), LOMLSPV ablation group (group 2, n=10), and LSG ablation group (group 3, n=10). Ablation was performed before occlusion of the left anterior coronary artery. Changes in the heart rate variability, serum norepinephrine, ventricular effective refractory period, and blood pressure induced by LSG stimulation were observed, and the occurrence of VAs was recorded. Immunostaining examinations of LOMLSPV were performed in dogs without ablation. Results: In group 2, LOMLSPV ablation evidently attenuated blood pressure elevation induced by LSG stimulation. Both LOMLSPV ablation and LSG ablation similarly prolonged ventricular effective refractory period and reduced the concentration of serum norepinephrine, the sympathetic index of heart rate variability, and the incidence of VAs compared with sham ablation. Abundant sympathetic nerve fibers were observed in LOMLSPV . Conclusions: LOMLSPV ablation prevented acute myocardial infarction–induced VAs with the same efficiency as LSG ablation, potentially by blocking the sympathetic pathway from the LSG to the heart.